Dinamika Ekosistem Tari Indang Tagak di Jorong Sampu Nagari Lubuk Gadang Utara Kabupaten Solok Selatan Provinisi Sumatera Barat - Wiri Septi Handayani; Erlinda Erlinda; Auliana Mukthi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This study aims to discuss the dynamics of the Indang Tagak dance ecosystem in Jorong Sampu Nagari Lubuk Gadang Utara, South Solok Regency, West Sumatra Province. The research method used is a qualitative method that is descriptive analysis. The theory used is Sal Murgianto's thoughts on healthy dance life in the dance environment itself and the theory of form by Y Sumandio Hadi. This theory is used to discuss the form of Indang Tagak dance performances in Jorong Sampu Nagari Lubuk Gadang Utara. The results of this study indicate that the Indang Tagak dance ecosystem in Jorong Sampu Nagari Lubuk Gadang Uatara, South Solok Regency has decreased. the dance ecosystem that is not given much attention by the local community and government agencies in South Solok Regency, so that there is an imbalance in the life of the dance itself in the South Solok community.